MORPHOLOGICAL, IMMUNOHISTOCHEMICAL AND SPECTRAL CHARACTERISTICS OF DYSPLASIA, PREINVASIVE AND INVASIVE FORMS OF LUNG CANCER - A. I. Arseniev; A. A. Barchuk; E. A. Zhelbunova; D. E. Matsko; A. S. Barchuk; E. V. Levchenko; K. E. Gagua; K. A. Kostitsyn; S. A. Tarkov; A. O. Nefyodov (Вестник хирургии имени И.И. Грекова)
An analysis of modern methods of diagnostics such as morphological, immunohistochemical and spectral, which included the bronchoscopy and spectrometry by using reflectance and autofluorescent regime, was made. The data involved the results of prospective follow-up study of 167 patients (620 biopsies). An obligatory spectrometry of suspicious area was carried out before the forceps biopsy. The microslides, which met the requirements of criteria of one of the carcinogen steps (n=201), were subjected to the in-depth morphological and immunohistochemical investigations. The tendency of angiogenesis (CD31 and CD34), proliferative activity (Ki-67), level of apoptosis (P53), EGFR expression were estimated. The sensitivity of combined endoscopic method was 94,74% by specificity 79,95% and high prognostic value of negative endoscopic diagnosis — 99,4%.